Legal Protection For Victims Of Cyber Crime Hacking Through Online Games According To Indonesian Regulations - Rizky, Muhammad (Recidive : Jurnal Hukum Pidana dan Penanggulangan Kejahatan, 2023)
This research aims to examine the problem of legal protection of personal data in online game accounts according to regulations in Indonesia. This research is a prescriptive normative legal research. This research uses a statutory approach. The data collection technique used by this research is literature study because this research uses secondary data as a source of research data whose sources are primary and secondary legal materials. This research uses qualitative data analysis techniques with a deductive thinking process. From this research, it is known that the regulations of cyber crime of hacking in Indonesia, in addition to formulating the criminal act, also formulates the legal protection of the cyber crime hacking victims. In general, the form of legal protection given to the victims of cyber crime hacking has the right to file criminal charges (procedural right). In addition, victims of cyber crime are entitled to restitution or compensation. In the case of hacking through online games, players whose accounts are stolen have the right to report the case to the authorities and are entitled to compensation from the online game developers in the form of a new account or whatever is stated in the EULA (End-User License Agreement) of the online games.